Some biochemical index of three sesame cultivars grown in the coastal sandy soil of Nghe An province - Vuong, Le Quang; Son, Hoang Van; Thieu, Phan Xuan (Academia Journal of Biology, 2014)
The oil contents, the oil and protein qualities of the seeds from three sesame cultivars (black, V6 and yellow cultivars) grown in 2003 in the Nghean province were determined. The rank of the oil content value of these three sesame cultivars was V6 (53.14%), yellow (50.64%) and black (43.10%). The free fatty acid values were 1.83, 3.49 and 3.88 for these V6, black and yellow cultivars respectively. The total amino acid contents (g/100g of seed) were 23.17, 22.83 and 20.89 in V6, yellow and black cultivars respectively. The seed amino acid composition and ratio were the same in these three sesame cultivars.